Dynamics in Health and Employment: Evidence from Indonesia - Subha Mani; Sophie Mitra; Usha Sambamoorthi (Institute for the Study of Labor (IZA), 2016)
This paper examines the consequences of disability, identifying for the first time, the separate impacts of onsets and recoveries from disability on both employment status and hours worked using panel data from Indonesia. We find that changes in physical functioning have no affect hours worked among the employed. However, we find that onsets of physical limitations lead to an increase in the probability of leaving employment, while recoveries increase the probability of returning to work. We also find a larger effect among self-employed workers compared to salaried workers. These results overall point towards a need for social protection policies with a focus on health, disability, and employment in Indonesia.
Keywords: I12; J32; J24; 330; health; disability; aging; employment; hours worked; Indonesia